Field notes contributed by Bery Engebretsen, summer 2002 - Engebretsen, Beryet al (2002)
Summer report of birds found in central Iowa contributed by Bery Engebretsen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 2002. Epson - sheet feed